Synthesis of Paeonol-Ozagrel Conjugate: Structure Characterization and In Vivo Anti-Ischemic Stroke potential - Zhang, Jing; Jiang, Miaomiao; Zhao, Hui; Han, Lan; Jin, Yu; Chen, Weidong; Wang, Jianqing; Zhang, Ziyu; Peng, Can (Frontiers in Pharmacology, 2021)
Ischemic stroke is a common neurological disease that can lead to mortality and disability. The current curative effect remains unsatisfactory because drug accumulation in the diseased areas is insufficient as a result of the unique blood–brain barrier. Therefore, much attention has been paid to develop a novel therapeutic compound, paeonol-ozagrel conjugate (POC), for ischemic stroke. Then, POC was successfully synthesized by conjugating of paeonol and ozagrel as mutual prodrug. A series of in vitro characterizations and evaluations, including high - resolution mass spectroscopy, nuclear magnetic resonance spectroscopy, partition coefficient, and assessment of cytotoxicity against PC12 cells, were performed. Pharmacokinetic study demonstrated POC is eliminated quickly (t1/2 = 53.46 ± 19.64 min), which supported a short dosing interval. The neurological score, infarct volume, histopathological changes, oxidative stress, inflammatory cytokines levels, and TXA2 levels also were evaluated in vivo in middle cerebral artery occlusion (MCAO) rats. All results showed that POC had a significant curative and therapeutic effect on ischemic stroke, as evaluated by the middle cerebral artery occlusion. Overall, POC can be expected to become a new drug candidate for the treatment of ischemic stroke.